The Analysis of the Nestlé Career Counselling Program for University Students and Graduates - Netolická, Veronika (2016)
The main goal of the thesis is to analyse the current situation of Nestlé Career Counselling program and make proposals which would lead to the increasing quality of this program. The thesis also stated to secondary aims. The thesis is structured into a theoretical and a practical part. The theoretical part of this thesis aims at mapping the theoretical background of Career Counselling. It is divided into two chapters. The First chapter describes the theoretical framework of Career Counselling including history of Career Counselling and Current Situation also describing the characteristics of Generation Y. The Second chapter describes Types of Career Counselling concentrating on Institutional and Corporate Career Counselling. The Practical part is also divided into two chapters. First the company Nestlé is described, including also the history and Nestlé needs youth initiative. The Last chapter deals with Nestlé Counselling, the development of the program is mapped and analysed. Furthermore, the analysis of statistical date and students´ survey were conducted. Finally, the SWOT analysis of the program is done and there have been made proposals for the year 2016.